PENGUATAN DAN PENGEMBANGAN POTENSI SOSIAL DI DESA DURENAN SIDOREJO MAGETAN - Ahmad Aziz Fuadi; Dul Sai'in (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
The focus of the service carried out by the team is strengthening and developing the potential of education, religion and UMKM in Durenan Village, Plaosan District, Magetan Regency. This service activity uses the ABCD or Asset Based Community Development (ABCD) approach which prioritizes the utilization of assets and potential that exist in the community. The five stages of ABCD include Discovery, Dream, Design, Define, Destiny. The results of the service stated that strengthening and developing social potential in Durenan Plaosan Magetan Village focuses on three areas, namely education, religion and UMKM. Where this takes into account internal assets or capabilities and also external community support. The team's activities, which are still at the initial level or mapping, are expected to be able to produce comprehensive data to develop existing social potential.